Faktor-Faktor yang Mempengaruhi Ibu Hamil dalam Melakukan Perawatan Payudara di Klinik Pratama Nirmala Medan Tahun 2023 - Afnida Zahara; Isyos Sari Sembiring; Lidia Lesti Mastiur; Sri Ermaliani Br Bangun; Nuriani Nuriani (Calory Journal Medical Laboratory Journal, 2024)
A pregnant woman is a woman who carries a fetus in her womb after being fertilized BACKGROUND by spermatozoa. Pregnancy is a special situation for a woman as a prospective mother, because during pregnancy there will be physical changes that affect her life. During pregnancy, many changes will occur, both physical, social and mental. Pregnant mothers must have adequate nutrition, because the nutrition they get will be used for themselves and their fetus. For pregnant women, basically all nutrients require supplementation, but what is often lacking is protein energy and several minerals such as iron (Pantiawati in Mulyani, 2017). Breast care is a health behavior. Health behavior (according to Skinner) is: "a person's response to stimuli related to illness and disease, the health service system, eating and drinking, and the environment" (Unimus, 2012). Becker describes health behavior into three domains, namely health knowledge, attitudes towards health, and health practices (Wikipedia, 2012). According to Lawrence Green (1980) in Notoadmodjo (2007) there are 2 factors that influence human behavior in terms of health, namely: internal factors which include knowledge, perception, emotions, motivation, socio-economics and culture, and external factors, namely the environment. So far, from the literature that researchers have examined, there have been many studies that discuss breast care behavior, both during the antenatal period and during pregnancy.OBJECTIVE To analyze the relationship between factors that influence pregnant women in carrying out breast care at the Pratama Nirmala Clinic in 2023. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted as a statistical test result of a significant relationship. RESULTS There is a significant relationship between the factors that influence pregnant women in carrying out breast care at the Pratama Nirmala Clinic in 2023. ADVICE is given for research and for research sites and for educational institutions regarding breast care